2020
DOI: 10.1371/journal.pone.0233879
|View full text |Cite
|
Sign up to set email alerts
|

An automated pipeline for the discovery of conspiracy and conspiracy theory narrative frameworks: Bridgegate, Pizzagate and storytelling on the web

Abstract: Although a great deal of attention has been paid to how conspiracy theories circulate on social media, and the deleterious effect that they, and their factual counterpart conspiracies, have on political institutions, there has been little computational work done on describing their narrative structures. Predicating our work on narrative theory, we present an automated pipeline for the discovery and description of the generative narrative frameworks of conspiracy theories that circulate on social media, and act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 66 publications
1
86
0
Order By: Relevance
“…In prior work [67], we have shown that the final network comprising subnodes and their relationship edges is not sensitive to the exact size and content of the contextual groups derived at this stage. This CG grouping, which we undertake prior to applying k-Means clustering on word embedding, enables us to distill the noun phrases into groups of phrases that have a semantic bias.…”
Section: A Graphical Narrative Model and Its Estimationmentioning
confidence: 83%
See 4 more Smart Citations
“…In prior work [67], we have shown that the final network comprising subnodes and their relationship edges is not sensitive to the exact size and content of the contextual groups derived at this stage. This CG grouping, which we undertake prior to applying k-Means clustering on word embedding, enables us to distill the noun phrases into groups of phrases that have a semantic bias.…”
Section: A Graphical Narrative Model and Its Estimationmentioning
confidence: 83%
“…We model narratives as generated by an underlying graphical model [67]. The narrative graph is characterized by a set of n nodes representing the actants, a set of r relationships R = {R 1 , R 2 , .…”
Section: A Graphical Narrative Model and Its Estimationmentioning
confidence: 99%
See 3 more Smart Citations